USM DVC RECEIVES DELEGATION FROM EMBASSY OF THE REPUBLIC OF LIBYA - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 14 April 2017 – The Universiti Sains Malaysia (USM) Deputy ViceChancellor (Academic & International), Professor Dr. Ahmad Farhan Mohd Sadullah received a courtesy visit from the Embassy of The People's Bureau of The Republic of Libya, today at the USM International Mobility and Collaboration Centre (IMCC).